CAN THE RAT LIVER MAINTAIN NORMAL BRAIN DHA METABOLISM IN THE ABSENCE OF DIETARY DHA?, - Rapoport, Stanley I. (2009)
BACKGROUND: Docosahexaenoic acid (DHA) is required for normal brain function. The concentration of DHA in the brain depends on both diet and liver metabolism. OBJECTIVE: To determine rat brain DHA concentration and consumption in relation to dietary n-3 (omega-3) polyunsaturated fatty acid (PUFA) content and liver secretion of DHA derived from circulating α-linolenic acid (α-LNA). DESIGN: Following weaning, male rats were fed for 15 weeks either: (1) a diet with a high DHA and α-LNA content, (2) an n-3 PUFA “adequate” diet containing 4.6% α-LNA but no DHA, or (3) an n-3 PUFA “deficient” diet containing 0.2% α-LNA and no DHA. Brain DHA consumption rates were measured following intravenous infusion in unanesthetized rats of [1-(14)C]DHA, whereas liver and brain DHA synthesis rates were measured by infusing [1-(14)C]α-LNA. RESULTS: Brain DHA concentrations equaled 17.6 μm/g, 11.4 μm/g and 7.14 μm/g in rats on diets 1, 2 and 3, respectively. With each diet, the rate of brain DHA synthesis from α-LNA was much less than the brain DHA consumption rate, whereas the liver synthesis-secretion rate was 5-10 fold higher. Higher elongase 2 and 5 and desaturase Δ5 and Δ6 activities in liver than in brain accounted for the higher liver DHA synthesis rates; these enzymes were transcriptionally upregulated in liver but not in brain of rats fed the deficient diet. CONCLUSIONS: While DHA is essential to normal brain function, this need might be covered by dietary α-LNA when liver metabolic conversion machinery is intact and the diet has a high α-LNA content.